In the palace of Loneliness - Ivaturi, Puja Ankitha (Stimulus: A Medical Humanities Journal, 2023)
Poem: "In the palace of Loneliness…" Once I was pulled into a dark world of nothingness, The more I tried to run away, the more I got absorbed into the mess. Turned around to walk alone, down an endless destination, In a stormy path, with the hope of reaching the sunshine. Waiting for the one, several sleepless nights got fade, Realized that, “To be human is to be alone”, no mate, no comrade! Sat on a rock, accompanying the music made by my heart. Finally! Getting an opportunity to feel this new life and interact. Became an invisible, motionless seed in a flower to the busy world, Wandering there, looking for the birds run by, concerned. Digesting the fact that, the world laughs with me but not weeps, Giggling at my fate, had covered my broken heart’s silent shrieks. There I stood with a determined heart and poor soul, Pondering towards the best yet to come, a true goal. Running, by shooing away the negative thoughts and things, To find the light of loveliness in the palace of loneliness.